TRACES OF GLACIAL ON MESCIT MOUNTAINS (NE TURKEY) - Nurfeddin KAHRAMAN (Fırat University, 2019)
Mescit Mountains reveal traces of Pleistocene glaciation. The presence of glacier erosion formations in the form of the cirque at the crest of such mountainous mass were determined during the explorations performed previously. During the observation we conducted in the region, the moraine deposits were determined, which were consisted of till sedimentations in Eskiköy, located at the upper course of Petekli Brook located close to southwest of the crest section. Located at heights of 1,800 to 1,880 m., Eskiköy features formation of the mixtures of the glacier and stream, with a wavy appearance due to the moraine accumulations on the surface. The moraine sets are located under the slopes of mountain range facing to the south, which surrounds that plane from the south and south-east and east sections of it, at heights of about 1,830 m to 1,870 m. At sections below specified mountain, these sets haven’t deteriorated under natural or human factors. It had named as Büyük and Küçük Henegen, the moraine sets located at these sections imply that they are recently formed, considering that they preserve their initial formations. Mescit Mountains is located in south of the Eastern Black Sea Mountains. Mentioned mountain ranges is located in close to each other and these raises exceeds 3,000 meters. In this regard, the Pleistocene glaciation process showed similarities on these mountains. Moraine sets in Eskiköy was considerably to fall into ruin by natural and human reasons. This fall into ruin is further in the former glacier sets. The traces of accumulation of Pleistocene glaciations observed at the regions near to the summit of Mescit Mountains is depicted with this work for the first time.